Pendampingan Penyusunan Lembar Refleksi Emosi sebagai Deteksi Dini kesehatan Mental dalam Penguatan Literasi Psikologi - Angeline Hosana Zefany Tarigan; Ruth Helen Simarmata; Danny Saputra; Indra Prapto Nugroho; Ria Thalia; Yeni Anna Appulembang (Jurnal Medika: Medika, 2026)
The strengthening of psychological literacy and early detection of students’ mental health in the school environment is especially important for adolescents who face academic, social, and boarding-school adjustment pressures. SMP Advent Palembang was selected as a partner because it needed a simple yet effective instrument to help teachers and dormitory supervisors understand students’ emotional conditions. This community service activity aimed to improve teachers’ understanding of psychological literacy and to assist in the development and implementation of the Emotion Reflection Sheet (Lembar Refleksi Emosi/LRE) as a tool for the early detection of students’ mental health issues. The implementation method included the stages of preparation, training, mentoring, implementation, and evaluation. The activities were carried out through lectures, discussions, instrument-development practice, and assistance in using the LRE in both printed and digital forms. The results showed that participants experienced improved understanding of psychological literacy, emotion regulation, and the importance of students’ emotional reflection. This program also produced outputs in the form of an Emotion Reflection Sheet and a simple dashboard to monitor students’ emotional patterns periodically. These findings indicate that the use of a simple reflective instrument can support the creation of a school culture that is more empathetic, responsive, and concerned with students’ psychological well-being.